A prospective study to determine epidemiology, predisposing factors and microbiology of keratitis in north India - Perween, Naz; Bisht, Dakshina; Chandran, Suprabha; Mohanty, Aroop; Kumar, Shyam K. (International Journal of Advances in Medicine, 2020)
Background: Corneal opacification due to keratitis is a leading cause of blindness, with fungal pathogens being important causative agents. Thus, a prospective study was designed to identify the etiological agents; and assess the epidemiological features and risk factors for infective keratitis in India with particular reference to fungal keratitis. Methods: Corneal scrapings were collected from 151 patients and subjected to direct microscopic examination by gram’s stain, KOH wet mount, followed by fungal culture in sabouraud’s dextrose agar and bacterial culture in MacConkey’s agar and blood agar. Identification of fungal growth was done by colony morphology, slide culture and lacto phenol cotton blue wet mount preparation. Results: Out of the 151 cases of keratitis, 65 (43.0%) showed fungal elements on KOH smear. By culture methods, microbial etiology (fungal/ bacterial) was established in 68 (45.0%) patients. Aspergillus spp. (57.7%) was the most frequently isolated fungus, followed by Fusarium (15.4%), Penicillium (7.7%), Curvularia (9.6%), Alternaria (5.8%) and Candida albicans (1.9%). History of trauma with vegetative and non-vegetative material and prior ophthalmologic intervention were the major identifiable risk factors. Conclusions: Thus, aspergillus spp. is the most common cause for fungal keratitis in India, with A. fumigatus and A. flavus being the most familiar species, followed by Fusarium. Bacterial isolates were responsible for considerably fewer cases of keratitis.